The Influence of Celebrity Endorser and Brand Image on Purchase Decisions of Wardah Cosmetics Consumers in Palembang City - Rizki Rahma Dona; Siti Komariah Hildayanti; Shafiera Lazuarni (International Journal of Marketing & Human Resource Research, 2022)
This study aims to determine: (1) the influence of celebrity endorsers on Wardah cosmetic purchasing decisions, (2) the influence of brand image on Wardah cosmetic purchasing decisions, and (3) the influence of celebrity endorsers and brand image on Wardah cosmetic purchasing decisions.This study uses a quantitative approach by collecting data through survey methods. The population in this study are consumers who have purchased and used Wardah cosmetics in Palembang City. The sample collection technique used purposive sampling method with criteria that included consumers who had purchased and used Wardah cosmetics in Palembang City and were aware of Wardah's advertisements. The sample is a minimum of 110 respondents with data collection techniques using a questionnaire through Google Form. Data analysis techniques in this study used descriptive analysis techniques, classical assumption test, multiple linear regression and hypothesis testing. The test was carried out using the help of SPSS 23.The results of this study indicate that: (1) celebrity endorser has a positive effect on purchasing decisions, as evidenced by the tcount value of 5.613 with a significance value of 0.000, less than 0.05 and the regression coefficient having a positive value of 0.562; (2) brand image has a positive effect on purchasing decisions, as evidenced by the t-value of 3.900 with a significance value of 0.000 less than 0.05 and a regression coefficient of 0.375; (3) celebrity endorser and brand image simultaneously have a positive effect on purchasing decisions, as evidenced by the Fcount of 36,390 with a significance value of 0.000 less than 0.05.